SUBJEKTIVITAS DALAM CERITA PERJALANAN NOVEL LUMBINI KARYA KRIS BUDIMAN - Novi Sri Purwaningsih (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
In the recent years, there are numerous books containing travel writing, both in Indonesia and abroad, have been published. The books can be a novel, memoir, travelogue, poetry, and short story. One of the novels containing travel writing is Lumbini written by Kris Budiman. It is about Ratna and Niko who travel to Nepal. Told in many points of view, this novel shows its subjectivities. In order to reveal this, the researcher will apply the concept of travel writing by Carl Thompson. Through the analysis, it is found that subject “I” in this novel is not a dependent subject because it, sometimes, is substituated with “we”. Besides, subject “I” also interact with other object. Thus, the subject can be classified as an “romantic self”. According to Thompson, it seemingly more open than Enlightenment self.Keywords: subjectivity, travel writing, romantic subject.